A study of celebrity endorser effectiveness in sport marketing among young Malaysian consumers / Nadia Yamina Rosli - Rosli, Nadia Yamina (2012)
The practice of using athletes to endorse sport and non-sport product has become a famous marketing strategy today. As a result of media coverage and increased vision, star athletes have put their celebrity status and benefited financially from endorsing products. Number of studies has found that a star athlete’s association with a brand may help to define and enhance the brand images, but the negative characteristics or information’s an endorser could have a fail effect (Till and Shimp, 1998; Koerning and Boyd, 2009). To influence consumer purchase intention is the success of endorser effectiveness. Therefore, the purpose of this study is to examine the effects on endorser effectiveness on consumer purchase intention by identification of an athlete and his or her sport, match-up concept (Expertise, Trustworthiness and Image) and perceived value of the product (Emotion, Quality, Price and Social). 135 participants were university students, who responded distributed questionnaire that measured their perception identification with the athlete and her sport, match-up between endorser and product, perceived value of the product, and purchase intentions after viewing an advertisement with Maria Sharapova endorsing a Canon PowerShot digital cameras. The factors analysis revealed that match-up concept was not support the objective and hypothesis of the study. However, other factors showed a favorable result. Generally, corporations when choosing athlete endorsers can use this study as a reference.